Obstructed infracardiac total anomalous pulmonary venous connection with patent ductus venosus: possibility of emergency palliation - Damandeep Singh; Niraj Nirmal Pandey; Joseph Thomas; Saurabh Kumar Gupta; Priya Jagia (The Egyptian Heart Journal)
Abstract Background Patients with obstructed infra-cardiac total anomalous pulmonary venous connection (TAPVC) require urgent intervention to relieve the obstruction, with or without restoration of anatomical continuity between the pulmonary veins and the left atrium. In cases of infra-cardiac TAPVC draining into the inferior vena cava (IVC) or hepatic vein, the obstructed channel can be accessed via the systemic venous approach for endovascular palliation. However, in cases of infra-cardiac TAPVC draining into the portal venous system, an endovascular approach to the obstructed channel is not possible via the transfemoral route and may require direct percutaneous puncture of the splenoportal axis. Case presentation A 45-day-old boy presented with acute respiratory distress and cyanosis. CT angiography demonstrated infra-cardiac TAPVC with a focal critical stenosis in the descending channel, just proximal to its confluence with the portal vein. Incidentally, a vascular channel connecting the left branch of the main portal vein and the intra-hepatic IVC suggestive of a patent ductus venosus was noted. The patent ductus venosus would allow access to the site of obstruction (transfemoral venous approach → IVC → patent ductus venosus → left portal vein → main portal vein → obstructed descending common channel) to achieve emergency palliation by dilating the obstructed segment and subsequently, stenting the ductus venosus to circumvent the distal obstruction at the portal venous sinusoids. Conclusion The present case highlights the role of CT angiography in delineating cardiovascular anatomy and demonstrating alternate vascular pathways that may be utilized for performing palliative endovascular procedures.